Tunable Schottky contact at the graphene/Janus SMoSiN2 interface for high-efficiency electronic devices. (26th January 2023) - Nguyen, Son-Tung; Nguyen, Cuong Q; Sin Ang, Yee; Phuc, Huynh V; Hieu, Nguyen N; Hiep, Nguyen T; Hung, Nguyen M; Phuong, Le T T; Hieu, Nguyen V; Nguyen, Chuong V
Abstract: The electrical contacts formed between the channel materials and the electrodes play a vital role in the design and fabrication of high-performance optoelectronic and nanoelectronic devices. In this work we propose combining metallic single-layer graphene (SLG) and a Janus SMoSiN2 semiconductor and investigate the electronic properties and contact types of the combined heterostructures (HTSs) using first-principles calculations. The effects of electric fields and interlayer coupling are also examined. The combined SLG/SMoSiN2 and SLG/N2 SiMoS HTSs are both structurally and thermodynamically stable at equilibrium interlayer coupling. The combination between SLG and a Janus SMoSiN2 semiconductor generates a p-type or n-type Schottky contact, depending on the stacking configuration. The SLG/SMoSiN2 HTS generates a p-type Schottky contact while the SLG/N2 SiMoS HTS forms an n-type one. Furthermore, applied electric field and strain can adjust the electronic features and contact types of the HTSs. An applied negative electric field and tensile strain lead to conversion from a p-type to an n-type Schottky contact in the SLG/SMoSiN2 stacking configuration, whereas a positive electric field and compressive strain give a transformation from an n-type to a p-type Schottky contact in the SLG/N2 SiMoS stacking configuration. Our findings provide rational evidence for the fabrication and design of electrical and optical devices based on SLG/SMoSiN2 HTSs.